2001
DOI: 10.1242/jcs.114.18.3273
|View full text |Cite
|
Sign up to set email alerts
|

Rho-dependent transfer of Citron-kinase to the cleavage furrow of dividing cells

Abstract: Citron-kinase (Citron-K) is a Rho effector working in cytokinesis. It is enriched in cleavage furrow, but how Rho mobilizes Citron-K remains unknown. Using anti-Citron antibody and a Citron-K Green Fluorescence Protein (GFP)-fusion, we monitored its localization in cell cycle. We have found: (1) Citron-K is present as aggregates in interphase cells, disperses throughout the cytoplasm in prometaphase, translocates to cell cortex in anaphase and accumulates in cleavage furrow in telophase; (2) Rho colocalizes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…CITK reaches its peak of expression during the G2/M phase of the cell cycle. It is nuclear during interphase, cytoplasmic at early prophase, enriched at spindle poles before anaphase, and is localized at the cleavage furrow and at midbody during cytokinesis [ 115 , 119 ] (Fig. 1 ).…”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
“…CITK reaches its peak of expression during the G2/M phase of the cell cycle. It is nuclear during interphase, cytoplasmic at early prophase, enriched at spindle poles before anaphase, and is localized at the cleavage furrow and at midbody during cytokinesis [ 115 , 119 ] (Fig. 1 ).…”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
“…It is important to highlight that all these events are coordinated by Rho1-GTP, which is continually generated at the equatorial plasma membrane during cytokinesis (Bement et al, 2005), by the RhoGEF Pebble/ECT2 (Somers and Saint, 2003), and which undergoes GTPase flux (Miller et al, 2008). Both sets of Anillin-scaffolded complexes described in the present study must be controlled by discrete pools of Rho1, since Rho1-GTP-bound Anillin is specifically required for anillo-septin assembly (and thus shedding) (Carim and Hickson, 2023), and Rho1-GTP-bound Citron kinase/Sticky is specifically required for MR formation (Eda et al, 2001; El-Amine et al, 2019; Watanabe et al, 2013). We provide evidence that both of these Rho1-dependent pathways contribute to Anillin localization.…”
Section: Discussionmentioning
confidence: 91%
“…This study revealed that NMII concentrates at the equatorial cortex and disappears from the poles during anaphase [ 242 ]. The small GTPase RhoA (Rho1 in Drosophila ) is known to control NMII by activating Rho kinase, which, in turn, phosphorylates RLC on Thr-18 and Ser-19 [ 243 , 244 , 245 , 246 ]. It has been proposed that NMII filaments concentrate at the equatorial cortex through a mechanism that requires Rho kinase-mediated RLC phosphorylation.…”
Section: Scaffolding Proteins and Phosphoinositide Binding Proteins C...mentioning
confidence: 99%